Non-metal framework for removable partial dentures - A 2-year follow-up clinical report - Gomes,Isabel (2024)
Abstract Traditional removable partial dentures (RPDs) with cobalt-chromium frameworks have been used for several decades, restoring the masticatory function. However, these frameworks have been documented as aesthetically unacceptable due to the display of metal clasps. The patients' increased demands regarding the aesthetic aspects of rehabilitation treatment led to the introduction of new, more aesthetic materials in clinical practice. One of the main materials is polyetheretherketone (PEEK). This clinical report presents PEEK as an alternative material for fabricating RPD frameworks for a Class III Kennedy partial edentulous mandible. The framework was constructed using CAD/CAM manufacturing, and the process combined laboratory scanning, digital framework design, resin try-in milling, and PEEK framework milling. The framework showed good adaptation to the abutment teeth and surrounding tissues. The patient was followed for 2 years without complaints and was grateful for the aesthetics. During this period, there were no signs of degradation in the framework, and the clasps were still as retentive as they were at the initial appointment, with only some pigmentation of the structure being observed.